Collective memory for American leaders: Measuring recognition for the names and faces of the US presidents. - Adam L Putnam (Public Library of Science (PLoS), 2021)
Collective memory studies show that Americans remember their presidents in a predictable pattern, which can be described as a serial position curve with an additional spike for Abraham Lincoln. However, all prior studies have tested Americans' collective memory for the presidents by their names. How well do Americans know the faces of the presidents? In two experiments, we investigated presidential facial recognition and compared facial recognition to name recognition. In Experiment 1, an online sample judged whether each of the official portraits of the US presidents and similar portraits of nonpresidents depicted a US president. The facial recognition rate (around 60%) was lower than the name recognition rate in past research (88%), but the overall pattern still fit a serial position curve. Some nonpresidents, such as Alexander Hamilton, were still falsely identified as presidents at high rates. In Experiment 2, a college sample completed a recognition task composed of both faces and names to directly compare the recognition rates. As predicted, subjects recognized the names of the presidents more frequently than the faces. Some presidents were frequently identified by their names but not by their faces (e.g. John Quincy Adams), while others were the opposite (e.g. Calvin Coolidge). Together, our studies show that Americans' memory for the faces of the presidents is somewhat worse than their memory for the names of the presidents but still follows the same pattern, indicating that collective memories contain more than just verbal information.